2020
DOI: 10.1016/j.isci.2020.101183
|View full text |Cite
|
Sign up to set email alerts
|

AUTS2 Regulation of Synapses for Proper Synaptic Inputs and Social Communication

Abstract: Impairments in synapse development are thought to cause numerous psychiatric disorders. Autism susceptibility candidate 2 (AUTS2) gene has been associated with various psychiatric disorders, such as autism and intellectual disabilities. Although roles for AUTS2 in neuronal migration and neuritogenesis have been reported, its involvement in synapse regulation remains unclear. In this study, we found that excitatory synapses were specifically increased in the Auts2-deficient primary cultured neurons as well as A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 82 publications
3
73
1
Order By: Relevance
“…By contrast, the number of USVs min −1 reported in other studies, including our previous study, is higher. For example, the mean number of approximately 250 min −1 [ 9 , 24 , 37 ] or approximately 100–150 min −1 [ 25 , 28 ] of male–female USVs, and approximately 150–200 min −1 of female–female USVs have also been reported [ 25 , 28 ]. In these studies, several days (up to 7 days) of single housing was carried out in both male and female subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the number of USVs min −1 reported in other studies, including our previous study, is higher. For example, the mean number of approximately 250 min −1 [ 9 , 24 , 37 ] or approximately 100–150 min −1 [ 25 , 28 ] of male–female USVs, and approximately 150–200 min −1 of female–female USVs have also been reported [ 25 , 28 ]. In these studies, several days (up to 7 days) of single housing was carried out in both male and female subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, vocal communication in mice has received considerable academic attention because of its power and utility in the investigation of molecular and neural mechanisms for social behaviours and their deficits, especially focusing on developmental disorders such as autism spectrum disorders [ 3 , 22 , 23 ]. For instance, in our previous study, mice carrying a mutation in the autism susceptibility candidate 2 (AUTS2) gene show an increase in excitatory synaptic inputs in the forebrain, as well as a reduction in their social interaction and vocalizations toward unfamiliar individuals [ 24 ]. Therefore, using both male and female mice, we aimed to observe alterations in USVs depending on different social contexts such as familiarity with social partners.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the mean number of approximately 250 / min (Kikusui et al, 2011;Kanno and Kikusui, 2018;Hori et al, 2020) or approximately 100-150 / min (Hammerschmidt et al, 2012;Ey et al, 2013) of male-female USVs, and approximately 150-200 / min of female-female USVs have also been reported (Hammerschmidt et al, 2012;Ey et al, 2013). In these studies, several days (up to 7 days) of single housing was carried out in both male and female subjects.…”
Section: Technical Limitations and Considerations For Experimental Dementioning
confidence: 99%
“…Recently, vocal communication in mice has attracted considerable academic attention because of its power and utility in the investigation of molecular and neural mechanisms for social behaviors and their deficits, especially focusing on developmental disorders such as autism spectrum disorders (Fischer and Hammerschmidt, 2011;Lahvis et al, 2011;Konopka and Roberts, 2016). In addition, we previously investigated synapses and behaviors in the mutants of Autism susceptibility candidate 2 (AUTS2) gene, and we reported that excitatory synaptic inputs were increased in the forebrain and that social interaction and vocalizations were altered in the mice (Hori et al, 2020). In mice, ultrasonic vocalizations (USVs) are used for communication, and they can be widely observed in both wild and laboratory strains (Sales, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…2. The Auts2 del8/+ pups with C57BL/6N background, which exon 8 of the Auts2 gene has been removed, were generated by Auts2 del8/+ male mice with wildtype female mice as the previous research [31]. After mating, each female mouse was separated from the male mouse.…”
Section: Experimental Animalsmentioning
confidence: 99%